MOLECULAR PHYLOGENY OF MAIDENHAIR FERN GENUS ADIANTUM (PTERIDACEAE) FROM LESSER SUNDA ISLANDS INDONESIA BASED ON RBCL AND TRNL-F - Lestari, Wenni Setyo; Adjie, Bayu; Jaruwatanaphan, Tassanai; Watano, Yasuyuki; Pharmawati, Made (REINWARDTIA, 2014)
The Lesser Sunda Islands of Indonesia are composed of small islands scattered from Bali to Timor Island. We analyzed a molecular phylogeny of Adiantum collected from Lesser Sunda Islands to reveal its phylogenetic relationships. A total of 12 species of Adiantum from this region and seven species from Java Island were collected and used in this study. Two cpDNA regions (rbcL and trnL-F) were chosen as markers and phylogenetic analyses were conducted using Neighbour-Joining (NJ) and Maximum Parsimony (MP) methods. The tree topologies reconstructed by NJ and MP from specimens used in this study and other species downloaded from GenBank are congruent in which trees are divided into five major clades. Adiantum species of Lesser Sunda Islands are not monophyletic and comprises three clades, i. e. Clade I composed of A. hispidulum group, Clade III composed of A. peruvianum group and Clade IV or A. caudatum group, each together with extra-Lesser Sunda samples. No sample from Lesser Sunda Islands examined is located in Clade II (A. tenerum group) and V (A. capillus-veneris group).